Cost-Effectiveness Assessment of Internet of Things in Smart Cities - Febrer, Nuria; Folkvord, Frans; Lupiañez-Villanueva, Francisco (Frontiers in Digital Health, 2021)
With the ongoing rapid urbanization of city regions and the growing need for (cost-)effective healthcare provision, governments need to address urban challenges with Smart City interventions. In this context, impact assessment plays a key role in the decision-making process of assessing cost-effectiveness of Internet of Things based Health Service Applications in cities, as it identifies the interventions that can obtain the best results. We present a new methodology to evaluate Smart City projects and interventions through the MAFEIP-tool, a recent online tool for cost-effectiveness analysis that has been used extensively to test ICT-solutions for healthy ageing. Resting on the principles of Markov’s model, the purpose of the MAFEIP tool is to estimate the outcomes of a large variety of social and technological innovations, by providing an early assessment of the likelihood of achieving anticipated impacts through interventions of choice. Thus, the analytical model suggested in this paper provides Smart City projects with an evidence-base assessment to improve their efficiency and effectivity, by comparing the costs and the efforts invested, with the corresponding results.